Implementasi High Press Paris Saint Germain: Analisis final liga champions 2025 vs inter Milan - Dimas Aditya; Rizki Apriliyanto; Ahmad Sulaiman (Universitas Hamzanwadi, 2026)
This study aims to provide an in-depth analysis of the implementation of the high-pressing strategy employed by Paris Saint-Germain (PSG) in the 2025 Champions League Final against Inter Milan. This tactical phenomenon is significant due to PSG’s success in neutralizing the opponent’s counterattacking patterns through a highly proactive defensive structure. Using a quantitative descriptive approach, this study analyzes match dynamics through systematic observation of video recordings and field zone mapping. The research instruments focused on three main variables: the intensity of pressure in the final third of the field, coordination between lines within the “inverted triangle” scheme, and the effectiveness of utilizing half-spaces to trigger positive transitions. The results indicate that the success of PSG’s high-pressing system relies not only on the players’ physical superiority but also on precise positional discipline to cut off the opponent’s vertical passing lanes. Key findings reveal that the transformation of the formation into an inverted triangle in midfield enables PSG to create pressing traps in the wing areas, forcing opposing players to make mistakes in dangerous zones. Visual data analysis via heatmaps confirms that pressing dominance is concentrated in the half-space areas. In conclusion, the integration of tactical intelligence and flexible positional structures. This study offers practical implications for coaches and tactical analysts in designing an aggressive yet organized defensive system.